Evaluation of quality and variety of Indonesian cassava (Manihot esculenta Crantz) - Amarullah, - (International Journal of Agricultural Research, Innovation and Technology, 2020)
The evaluating cassava varieties for productivity necessary to assess the cassava stem characteristics for their suitability as planting material and to improve the capability of cassava farmers to select good quality cassava varieties. Cassava varieties are generally distinguished from each other by their morphological characteristics, which include leaf, stem and tuber colour. The cassava planting material used in this study and some of characteristics by five cassava varieties, consisted of mature stem cuttings of about 20 cm in length, containing between 10 and 12 nodes and planted in a vertical position along the top of the ridges. Each plot consisted of 30 plants, with date being taken from ten plants within each plot. Cassava varieties Malang-6 presented the highest yield average is 13.81 tones ha-1 followed by Singgah and Adira-4 i.e. 11.98 t ha-1 and 11.11 t ha-1 of different varieties 1 yang Ketan, which only weighs 6.63 t ha-1. Harvest index varieties of Adira-4, Malang-6, UJ 5 and Singgah were found 0.78, 0.77, 0.77 and 0.76, respectively higher and significantly different IP varieties of glutinous Ketan is 0.58. Malang varieties and Malang-6 that produces the highest tuber weight, has a low dry matter content is 5.65% and 5.62%. The Ketan varieties and UJ-5 has a tuber weight was significantly lower with dry matter content higher than that dried 8.69% and 8.68%. The UJ-5 varieties has a tuber weight starch HCN 230,17 higher and significantly other variety. Int. J. Agril. Res. Innov. Tech. 10(1): 108-116, June 2020